Prevalence, Abundance, and Virulence of Adherent-Invasive Escherichia coli in Ulcerative Colitis, Colorectal Cancer, and Coeliac Disease - López-Siles, Mireia; Camprubí-Font, Carla; Gómez del Pulgar, Eva M.; Sabat Mir, Miriam; Busquets, David; Sanz, Yolanda; Martinez-Medina, Margarita (Frontiers in Immunology, 2022)
Background & aims: Adherent-invasive E. coli (AIEC) has largely been implicated in the pathogenesis of Crohn’s disease (CD). E. coli strains with similar genetic backgrounds and virulence genes profiles have been associated with other intestinal disorders, such as ulcerative colitis (UC), colorectal cancer (CRC), and coeliac disease (CeD), but the role of AIEC in these diseases remains unexplored. We aimed to assess the distribution, abundance, and pathogenic features of AIEC in UC, CRC, and CeD. Methods: The AIEC phenotype was investigated in 4233 E. coli isolated from the ileum and colon of 14 UC and 15 CRC patients and in 38 fecal E. coli strains obtained from 17 CeD and 10 healthy (H) children. AIEC prevalence and abundance were compared with previous data from CD patients and H controls. Clonality, virulence gene carriage, and phylogenetic origin were determined for the AIEC identified. Results: In UC, AIEC prevalence was intermediate between CD and H subjects (UC: 35.7%, CD: 55.0%, H: 21.4%), similar to CD patients with colonic disease (C-CD: 40.0%). In CRC, the prevalence was lower (6.7%). In patients with AIEC, the estimated abundance was similar across all intestinal conditions. All AIEC strains isolated from UC and CRC belonged to the B1 phylogroup, except for a strain of the A phylogroup, and the majority (75% of clonally distinct AIEC) harbored the Afa/Dr operon and the cdt gene. None of the E. coli isolated from the CeD cohort were AIEC. Nonetheless, E. coli strains isolated from active CeD patients showed higher invasion indices than those isolated from H and inactive CeD paediatric patients. Conclusion: We support the hypothesis that AIEC-like strains can be involved not only in CD but also in UC. Further works are needed to study the virulence particularities of these groups of strains and to determine if there is a causative link between AIEC and UC. In contrast, we rule out the possible association of AIEC with CRC but consider it of interest to further study the E. coli strains in CeD for their possible pathogenic role.